(untitled) (Clinics, 2013)
The use of non-ejaculated sperm coupled with intracytoplasmic sperm injection has become a globally established procedure for couples with azoospermic male partners who wish to have biological offspring. Surgical methods have been developed to retrieve spermatozoa from the epididymides and the testes of such patients. This article reviews the methods currently available for sperm acquisition in azoospermia, with a particular focus on the perioperative, anesthetic and technical aspects of these procedures. A critical analysis of the advantages and disadvantages of these sperm retrieval methods is provided, including the authors' methods of choice and anesthesia preferences.